Acute Pain Nursing Care (Minor Head Injury) With Head Up 30 ̊ Position at RSUD Dr. R. Soedarsono Pasuruan - Divanda Jasmine Aulia Surianto (International Journal of Health Engineering and Technology, 2025)
This study aims to describe the effectiveness of the 30° head-up position as a nursing intervention for managing acute pain in patients with a mild head injury (MHI). Although MHI is a prevalent neurological issue, there is limited research on non-pharmacological interventions for its associated acute post-traumatic headaches. Employing a descriptive qualitative approach with a single case study design, the research focused on one adult participant selected via purposive sampling at Dr. R. Soedarsono Hospital, Pasuruan. Data were collected using a triangulation method, including semi-structured interviews, physical observation, and documentation, and analyzed descriptively to identify key patterns. The findings demonstrated a significant reduction in the patient’s pain, with the Visual Analogue Scale (VAS) score decreasing from 5 to 3 over three days. The intervention also improved the patient’s sleep quality and stabilized vital signs. In conclusion, the 30° head-up position is a valuable and effective non-pharmacological nursing intervention for acute pain management in MHI patients, offering a promising alternative to traditional methods. However, the single case study design limits the generalizability of these findings.